CNS function and dysfunction during exposure to hyperbaric oxygen in operational and clinical settings - Geoffrey E. Ciarlone; Christopher M. Hinojo; Nicole M. Stavitzski; Jay B. Dean (Redox Biology, 2019)
Hyperbaric oxygen (HBO2) is breathed during hyperbaric oxygen therapy and during certain undersea pursuits in diving and submarine operations. What limits exposure to HBO2 in these situations is the acute onset of central nervous system oxygen toxicity (CNS-OT) following a latent period of safe oxygen breathing. CNS-OT presents as various non-convulsive signs and symptoms, many of which appear to be of brainstem origin involving cranial nerve nuclei and autonomic and cardiorespiratory centers, which ultimately spread to higher cortical centers and terminate as generalized tonic-clonic seizures. The initial safe latent period makes the use of HBO2 practical in hyperbaric and undersea medicine; however, the latent period is highly variable between individuals and within the same individual on different days, making it difficult to predict onset of toxic indications. Consequently, currently accepted guidelines for safe HBO2 exposure are highly conservative. This review examines the disorder of CNS-OT and summarizes current ideas on its underlying pathophysiology, including specific areas of the CNS and fundamental neural and redox signaling mechanisms that are thought to be involved in seizure genesis and propagation. In addition, conditions that accelerate the onset of seizures are discussed, as are current mitigation strategies under investigation for neuroprotection against redox stress while breathing HBO2 that extend the latent period, thus enabling safer and longer exposures for diving and medical therapies. Keywords: CNS oxygen toxicity, Hyperoxia, Reactive oxygen and nitrogen species, Brainstem, Seizure genesis, Seizure mitigation